The ANALISIS PENGARUH DAN TREN REALISASI PAJAK HOTEL SERTA PERTUMBUHAN JUMLAH WISATAWAN SEBAGAI VARIABEL MODERASI TERHADAP PENDAPATAN ASLI DAERAH KOTA MANADO - Lakat, Junior (FEB Universitas Sam Ratulangi Manado, 2023)
The study aims to analyze the trend of hotel tax receipts and explain its impact on the original income of the Manado region in 2019–2021, with the growth of the number of tourists as a variable of moderation. It was found that hotel taxes had a significant impact on the original income of the Manado area. As for the results of moderation tests using the absolute differential method, it was found that the growth in the number of tourists did not strengthen the reception of hotel tax against the PAD. The effect of the hotel tax on local real income indicates there are other types of tax and remuneration that were influential but have not been included in this study, so it is a recommendation to be added to further research.